2022
DOI: 10.2147/ijgm.s366956
|View full text |Cite
|
Sign up to set email alerts
|

Association Between TCF21 Gene Polymorphism with the Incidence of Paroxysmal Atrial Fibrillation and the Efficacy of Radiofrequency Ablation for Patients with Paroxysmal Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common sustained arrhythmia with a high rate of recurrence after catheter ablation. The gene encoding transcription factor 21 (TCF21) has been linked to coronary artery disease risk by human genome-wide association studies in multiple racial ethnic groups. However, the association of TCF21 with AF remains unclear. Patients and Methods: Circulating leukocytes in patients with paroxysmal AF (PAF) and 92 age-matched controls without a history of cardiovascular disease, AF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a recent study, it was found that the G allele and GG genotype of rs12190287 in TCF21 and the increase of TCF21 concentration were significantly associated with the occurrence of PAF and recurrence after ablation. TCF21 rs12190287 polymorphism can regulate the expression of TCF21, and the G allele and GG genotype of rs12190287 are associated with the pathogenesis and recurrence of PAF [95]. This suggests that TCF21 rs12190287 polymorphism may be a potential marker of genetic susceptibility to PAF onset and recurrence after catheter ablation in the Chinese population.…”
Section: The Role Of Tcf21 In Other Cardiovascular Diseasesmentioning
confidence: 99%
“…In a recent study, it was found that the G allele and GG genotype of rs12190287 in TCF21 and the increase of TCF21 concentration were significantly associated with the occurrence of PAF and recurrence after ablation. TCF21 rs12190287 polymorphism can regulate the expression of TCF21, and the G allele and GG genotype of rs12190287 are associated with the pathogenesis and recurrence of PAF [95]. This suggests that TCF21 rs12190287 polymorphism may be a potential marker of genetic susceptibility to PAF onset and recurrence after catheter ablation in the Chinese population.…”
Section: The Role Of Tcf21 In Other Cardiovascular Diseasesmentioning
confidence: 99%
“…Moreover, a Japanese study reported that TCF21 rs12190287 (G→C) may be a susceptibility locus for hypertension [24]. Another study found significant associations between the GG genotype and G allele of rs12190287 in TCF21 and an increased TCF21 concentration with the onset and recurrence of paroxysmal atrial fibrillation post ablation [25]. Considering these findings, study aimed to further explore whether TCF21 genetic polymorphisms affected susceptibility to stable angina and ST elevation myocardial infarction (STEMI) and their relationships with clinical and biochemical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…While many variants have been identified and replicated in other studies, these variants were identified when comparing all included cases of AF or MI with healthy controls. Some studies have been conducted with the aim of understanding the genetic of patients experiencing recurrent events of AF (1, 7, 8, 9, 10) and MI (11, 12, 13). These are, however, mostly focused on either (A) response after treatment, or (B) the genetic effects on recurrence from known AF/MI variants or genes.…”
Section: Introductionmentioning
confidence: 99%